Novel Genotype Definition and the First Epidemiological Investigation of Canine Adenovirus Type 2 in Dogs in Central China - Ji, Jun; Li, Wanyu; Hu, Wen; Xu, Xin; Kan, Yunchao; Yao, Lunguang; Bi, Yingzuo; Xie, Qingmei (Frontiers in Veterinary Science, 2020)
Infections caused by canine adenovirus (CAdV) type 1 have been reported worldwide in the past two decades. However, only few studies have specifically reported the prevalence of CAdV type 2 (CAdV-2). The present study investigated the persistent circulation of CAdV-2 in dogs with diarrhea in the Henan, Hubei, and Jiangsu provinces in central China from 2017 to 2019. We conducted polymerase chain reaction for detecting CAdV-2 and other related pathogens in 224 rectal swabs of pet dogs and the co-infection of canine diseases was also analyzed. In addition, the structural protein genes—Fiber, Hexon, and Penton—of the isolated CAdV-2 strains were sequenced and analyzed. The similarity between Hexon and Penton among the 19 strains was 97.4%, as revealed by sequence alignment. Multiple sequence alignment results showed that the Fiber gene sequences of these CAdV-2 strains shared 97.4%–99.8% nucleotide and 94.1%–99.3% amino acid identity with reference sequences and shared only 79.0%–80.5% nucleotide and 77.3%–80.5% amino acid identity with the vaccine strain CLL, indicating that Fiber harbored most of the variant sites. Furthermore, pairwise sequence comparisons of Hexon of CH-JS-1901 and CH-HN-1801 with that of India2006 revealed a novel genotype. Furthermore, protein model prediction showed that the amino acid mutation of fiber protein in 19 strains was located in the head region, that may cause structural changes on the surface of the fiber protein. These findings are of significance for monitoring the epidemiology of CAdV-2 infection and developing a novel vaccine which contribute to understanding genetic evolution of CAdV-2 in China.